Legal Analysis of the Judge’s Considerations in Verdict No. 34/Pid.Sus-TPK/2025/PN Jkt.Pst on Corruption in the Case of Raw Crystal Sugar Imports - Hariyanto, Soeko (Proceedings of International Conference of Graduate School on Sustainability, 2026)
Many acts of corruption in Indonesia involve officials who, in their positions, have the authority to commit such acts. One of the criminal acts of corruption in the court is the case No. 34/Pid.Sus- TPK/2025/PN Jkt.Pst concerning Criminal Acts of Corruption in the Case of Raw Crystal Sugar Imports involving the former Minister of Trade in 2015-2016, Tom Lembong. The court ruling states that Tom was found to have committed a criminal offense in accordance with the elements set out in Article 2 of the Corruption Eradication Law, in conjunction with Article 55(1) of the Criminal Code. Tom Lembong’s actions, which contravened several applicable legal provisions, were deemed unlawful. However, the facts of the trial showed that there was no mens rea and that there was confusion in calculating the value of state losses. This raised doubts about the court ruling that will be examined further in this article. The method used in this article is a normative legal method with a statutory approach, based on the collection of various legal sources, including statutory regulations, books, and scientific journals, which are reviewed to understand the application of mens rea in proving acts of corruption by Tom Lembong. The article concludes that the lack of proof of criminal intent (mens rea) at trial led the panel of judges to issue an inappropriate verdict against the defendant, Tom Lembong.